2023
DOI: 10.3390/antiox12040890
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Antioxidant Phytochemicals on Endogenous Antioxidants Defences in Chronic Diseases

Abstract: Chronic diseases and cancer are worldwide health problems which result in death and disability for millions of people [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…Unique polyphenol subgroups found in whole grain rice of various colors have a favorable effect on human health [1]. Increased whole grain consumption is strongly linked to a lower prevalence of chronic illnesses, according to the numerous epidemiological research [24]. Recent studies have shown that colored rice has high levels of antioxidants [2], which were identified by various cutting-edge method as ultra-performance liquid chromatography (UPLC), high-performance liquid chromatography (HPLC), liquid chromatography-mass spectrometry, ultra-HPLC Online-ABTS system.…”
Section: Bioactive Compounds In Pigmented Rice Cultivarsmentioning
confidence: 99%
“…Unique polyphenol subgroups found in whole grain rice of various colors have a favorable effect on human health [1]. Increased whole grain consumption is strongly linked to a lower prevalence of chronic illnesses, according to the numerous epidemiological research [24]. Recent studies have shown that colored rice has high levels of antioxidants [2], which were identified by various cutting-edge method as ultra-performance liquid chromatography (UPLC), high-performance liquid chromatography (HPLC), liquid chromatography-mass spectrometry, ultra-HPLC Online-ABTS system.…”
Section: Bioactive Compounds In Pigmented Rice Cultivarsmentioning
confidence: 99%
“…In general, the existence of hydroxyl groups is mainly responsible for the antioxidant capacity of phenolic compounds, which possess the ability to donate electrons [13]. These phenolic compounds also boost the antioxidant activities of cells by stimulating the synthesis of endogenous antioxidant molecules like glutathione peroxidase, superoxide dismutase, and catalase within the cell and inducing their defense mechanisms through the regulation of multiple signaling pathways [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Several existing studies have revealed that phenolic substances can suppress the generation of free radicals, break down peroxides and inactive metal ions, and hinder the process of oxygen scavenging within biological systems that ultimately defend against many oxidative diseases [17]. Thus, phenolic compounds from medicinal plants have recently gained extensive attention because of their plentiful pharmacological actions such as preventing neurodegenerative diseases, body inflammation, cancers, diabetes, osteoporosis, and cardiovascular problems [14]. Given the intrinsic utility and broad spectrum of potential uses in the pharmaceutical sector, it is crucial to concentrate on phenolic extraction.…”
Section: Introductionmentioning
confidence: 99%